2013
DOI: 10.3109/08820139.2013.806542
|View full text |Cite
|
Sign up to set email alerts
|

The effect of CD33 expression on inflammatory response in chronic obstructive pulmonary disease

Abstract: The granulocytes and monocytes in peripheral blood were activated in patients of acute exacerbation in COPD. CD33 on granulocytes had the potential to inhibit inflammation and prevent tissue damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Each procedure is performed for 3 minutes, once a day, until a local acid bilge feeling is reported. Studies 29 suggest that Tuina can improve lung function and the quality of life of patients with COPD; this finding is consistent with the results of this meta-analysis. Apart from Tuinaology, acupuncture treatment is also important for COPD patients' rehabilitation.…”
Section: Discussionsupporting
confidence: 82%
“…Each procedure is performed for 3 minutes, once a day, until a local acid bilge feeling is reported. Studies 29 suggest that Tuina can improve lung function and the quality of life of patients with COPD; this finding is consistent with the results of this meta-analysis. Apart from Tuinaology, acupuncture treatment is also important for COPD patients' rehabilitation.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, RNASeq data were collected for the cell markers CD33, CD68 and CD83. These data were used to assess gene expression markers for neutrophils (Zhang et al 2013), macrophages (Micklem et al 1989) and dendritic cells (Zhou and Tedder 1996), respectively. (The normalized gene expression files that were downloaded from the TCGA data portal were used to obtain the RNA expression levels for each of the three cell surface markers for each tumor type.)…”
Section: Methodsmentioning
confidence: 99%
“…HSCs undergo a massive increase in numbers in vivo during the process of hematopoietic reconstitution after stress, such as from infection, lipopolysaccharide challenge, chemotherapy, radiation, or transplantation [20,21], but this still cannot be recapitulated by ex vivo expansion approaches. Over the past decade, several novel studies have suggested that HSC expansion ex vivo might be feasible has led to a better understanding of specific factors regulating HSC self-renewal in vivo, and which have led to novel strategies to increase CD 34 enriched cells in ex-vivo [22,23].…”
Section: Discussionmentioning
confidence: 99%